2017
DOI: 10.1242/dev.149724
|View full text |Cite
|
Sign up to set email alerts
|

Adenohypophysis placodal precursors exhibit distinctive features within the rostral preplacodal ectoderm

Abstract: Placodes are discrete thickenings of the vertebrate cranial ectoderm that generate morpho-functionally distinct structures, such as the adenohypophysis, olfactory epithelium and lens. All placodes arise from a horseshoe-shaped preplacodal ectoderm in which the precursors of individual placodes are intermingled. However, fate-map studies indicated that cells positioned at the preplacodal midline give rise to only the adenohypophyseal placode, suggesting a unique organization of these precursors within the prepl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The pituitary is an evolutionarily conserved neuroendocrine organ of significant physiological importance. It has been well accepted its main tissue components, the AH and the NH, originate from the embryonic oral ectoderm and the neural ectoderm, respectively (De Beer, 1924; Herring, 1908; Sanchez-Arrones et al, 2017). Here, while dissecting the molecular attributes of zebrafish pituitary at a single cell level, we revealed that in contrast to the prevailing dogma, neural plate progenitors contribute to both adenohypophyseal and neurohypophyseal cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pituitary is an evolutionarily conserved neuroendocrine organ of significant physiological importance. It has been well accepted its main tissue components, the AH and the NH, originate from the embryonic oral ectoderm and the neural ectoderm, respectively (De Beer, 1924; Herring, 1908; Sanchez-Arrones et al, 2017). Here, while dissecting the molecular attributes of zebrafish pituitary at a single cell level, we revealed that in contrast to the prevailing dogma, neural plate progenitors contribute to both adenohypophyseal and neurohypophyseal cell types.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that although the pre-placodal ectodermal origin of the AH cells is well established (Couly and Le Douarin, 1988; Dutta et al, 2005; Kouki et al, 2001; Sanchez-Arrones et al, 2017), two studies using radiolabeling in Xenopus or analyzing quail grafted-chick chimeras have suggested that portions of anterior neural ridge (ANR), namely the most anterior neural tissue that meets the non-neural ectoderm, gives rise to at least a part of the adenohypophyseal cells (Couly and Le Douarin, 1985; Eagleson et al, 1986). However, the methods used in these studies lacked single cell resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory modalities did not all arise at the same time, thus supporting a potentially non-uniform development and function of sensory systems in modern vertebrates where there are substantial differences between placodes in terms of early development, organogenesis and integration in the nervous system. For example, recent studies examining adenohypopyseal placode development have shown an early cellular and molecular heterogeneity where the cellular morphology and gene expression patterns are distinct from that of the flanking "pre-placode" domain, (Sanchez-Arrones et al, 2017).…”
Section: Are All Placodes the Same?mentioning
confidence: 99%
“…(Couly and Le Douarin, 1985, Couly and Le Douarin, 1987, D'Amico-Martel and Noden, 1983, Noden, 1992, focusing on stages just before or after placodes become morphologically distinct. More recent studies investigating the origin of placodes showed that a continuous and unique territory of sensory progenitors can first be identified at head process stages (Bhattacharyya et al, 2004, Sanchez-Arrones et al, 2017, Streit, 2002, Xu et al, 2008: labelling experiments reveal a continuous band of ectoderm surrounding the anterior neural plate that contains precursors for all sensory placodes and has therefore been termed the pre-placodal region (PPR). An equivalent territory has also been identified by fate mapping experiments in Xenopus and fish (Bhat and Riley, 2011, Dutta et al, 2005, Kozlowski et al, 1997, Pieper et al, 2011.…”
Section: The Pre-placodal Region: a Unique Territory Of Sensory Placomentioning
confidence: 99%